The role of progesterone receptor isoforms in the myometrium. Issue 224 (November 2022) - Li, Wan-Ning; Dickson, Mackenzie J.; DeMayo, Francesco J.; Wu, San-Pin
Abstract: Myometrial contraction is stringently controlled throughout pregnancy and parturition. Progesterone signaling, effecting through the progesterone receptor (PR), is pivotal in modulating uterine activity. Evidence has shown that two major PR isoforms, PR-A and PR-B, have distinct activities on gene regulation, and the ratio between these isoforms determines the contractility of the myometrium at different gestational stages. Herein, we focus on the regulation of PR activity in the myometrium, especially the differential actions of the two PR isoforms, which maintain uterine quiescence during pregnancy and regulate the switch to a contractile state at the onset of labor. To demonstrate the PR regulatory network and its mechanisms of actions on myometrial activity, we summarized the findings into three parts: Regulation of PR Expression and Isoform Levels, Progesterone Receptor Interacting Factors, and Biological Processes Regulated by Myometrial Progesterone Receptor Isoforms. Recent genomic and epigenomic data, from human specimens and mouse models, are recruited to support the existing knowledge and offer new insights and future directions in myometrial biology. Highlights: Progesterone via the progesterone receptor (PR) controls uterine contractions. PR isoforms and cofactors together permit a wide spectrum of progesterone actions. Isoform-specific protein levels and modifications contribute to overall PR activities. Myometrial PR-A and PR-B confer divergent cellular actions via unique target genes.